IMPROVEMENT PRODUK HAMMOCK SLEEPING BAG DENGAN METODE QFD (QUALITY FUNCTION DEPLOYMENT) - Ahmad Kasan; Antoni Yohanes (Jurnal Ilmiah Dinamika Teknik, 2017)
This research was conducted in order to develop products Hammock Sleeping Bag manufactured by